Environmental Federalism : A Panacea or Pandora’s Box for Developing Countries? - Fredriksson, Per G.; Mani, Muthukumara; Wollscheid, Jim R. (World Bank, Washington, DC, 2012)
This paper provides new empirical evidence to the debate on the optimal locus of power over environmental policymaking in developing countries. The authors develop a simple lobby group model with mobile capital. The model predicts that a decentralized institutional structure leads to weaker environmental policy due to more intensive lobbying by capital owners and workers. They test this prediction using novel cross-sectional developing country data. The results are consistent with the prediction of the model, in particular for air pollution policies. The authors also find that the effect of decentralization declines with a greater degree of trade openness. They believe this is the first developing country evidence on the environmental policy effects of federalism.